A new hydrogen-based phase change material open-cycle micro engine. (18th May 2017) - Lidor, A.; Zibitsker, A.; Weihs, D.; Sher, E.
Abstract: A phase change material (PCM) open-cycle engine is a distinctive cycle that uses the ambient air as its hot reservoir and an on-board hydrogen storage as its cold reservoir. Here we present a new PCM open cycle engine, that is capable of overcoming two major problems of PCM engines: the significant energy losses at partial loads, and the power control inherent difficulties. The present new concept decouples the liquid boiling heating process from the vapors superheating stage. While this system is inherently unstable (as other PCM systems), it is shown that it can be effectively controlled with a simple proportional–integral controller. Highlights: A novel hydrogen-based phase change material open-cycle is proposed as an energy source. Many potential applications in small systems due to the specific power and specific energy of the system. The ambient air is used as its hot reservoir. The inherent instabilities of the systems can be easily controlled.